CADAR DALAM KONTEKS KEKINIAN PERSPEKTIF FILSAFAT HUKUM ISLAM - Puspita Sari, Rekha; Busyro, Busyro (Borneo : Journal of Islamic Studies, 2023)
The veil, or hijab, is one of the teachings of Islam intended for Muslim women. The law on wearing the veil for Muslim women is debated by scholars; some make it mandatory; it is sunnah; and there are scholars who determine the law is permissible. This research aims to review the legal issue of wearing the veil from the perspective of Islamic legal philosophy. This type of research is library research using a qualitative approach. Data collection was carried out by reading research sources in the form of books, journals, and relevant readings, which were then analyzed using descriptive techniques. This research found that wearing a veil for a woman produces maslahah at the tahsiniyah level because the woman will be more protected, both from the evil side of other people and in terms of protecting her face from things that disturb her beauty. Therefore, philosophically, the law of wearing the veil is at the level of sunnat (recommended).